Improved Phosphorus Bioavailability in Lettuce Crop via Naganishia albida Inoculation of Wastewater-Derived Struvite - Valentina Carrillo; Rodrigo Pérez; Felipe González; Christian Santander; Antonieta Ruiz; Eduardo Holzapfel; Pablo Cornejo; Gladys Vidal (Agronomy)
Phosphorus (P) is a vital element for optimal crop growth and agricultural productivity. Struvite, a P precipitate obtained from wastewater, is recognized as a slow-release, low-solubility fertilizer. The objective of this study was to evaluate the impact of inoculation with the yeast Naganishia albida on P bioavailability using struvite and triple superphosphate (TSP) in lettuce (Lactuca sativa L.) plants. Struvite fertilization improved N and P assimilation by 14–28% and 12–27%, respectively, compared to TSP and increased soil soluble P by 50% more than TSP and 186% more than the control. Inoculation reduced oxidative stress by 40–44%, improved plant growth by 28% with struvite and 7% with TSP, and increased acid phosphatase activity by 52.7% and 78.1%, respectively, improving nutrient bioavailability. Struvite showed high P solubility in the soil, with only a 3% difference between inoculated and non-inoculated treatments. In addition, the combination of fertilizer and yeast had a synergistic effect, increasing enzyme activity up to 1.8 times for struvite and 2.3 times for TSP. The results highlight the potential of struvite as a recycled fertilizer and the effectiveness of integrating fertilization with microorganisms to improve agricultural efficiency, reduce environmental impact and promote sustainable management in the framework of the circular economy.